Exploring Outdoor Classes Writing Creativity: Teaching Writing at the Seventh Graders in EFL Context - Anggraini, Adelia Septian; Prasetyarini, Aryati (JALL (Journal of Applied Linguistics and Literacy), 2025)
This study explores the learning of writing outside the classroom to explore or ideas in writing especially in English. The purpose of this study is to improve students' creativity and convey ideas through writing skills, especially in English, using learning methods in the form of activities outside the classroom for seventh-grade students in one of the Islamic schools in Surakarta. In addition, the purpose of this study is to analyze the opinions of students and teachers regarding the implementation, efficiency, and effectiveness of the use of learning methods outside the classroom by teachers for students to improve recount text writing skills in English subjects. The participants in this study were seventh-grade students totaling 21 with 14 female and 7 male, and 3 teachers from one of the Islamic schools in Surakarta. Data collection techniques used include observation, interviews, and documentation. The data collection instruments used were observation sheets, also question sheets for interviews. The data analysis technique used qualitative data analysis, with data collection methods in the form of interviews with participating parties and the results of field observations. And some supporting documents from this research. The success criteria of this study are seen from the results of interviews, and observations, as well as the process and results of recount text writing skills.